2022
DOI: 10.3390/atmos13060970
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Imidazole Compounds in Aqueous Secondary Organic Aerosol Generated from Evaporation of Droplets Containing Pyruvaldehyde and Inorganic Ammonium

Abstract: Imidazole compounds are important constituents of atmospheric brown carbon. The imidazole components of aqueous secondary organic aerosol (aqSOA) that are generated from the evaporation of droplets containing pyruvaldehyde and inorganic ammonium are on-line characterized by an aerosol laser time-of-flight mass spectrometer (ALTOFMS) and off-line detected by optical spectrometry in this study. The results demonstrated that the laser desorption/ionization mass spectra of aqSOA particles that were detected by ALT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…However, the intensity of the carbonyl group maximum absorption (λ max ) depends not only on the nature of substituent around the aldehyde/ketone group but also on the pH and the type of solvent. Several studies have been done on the pH dependency; in 2-IC for instance, the aldehyde group will hydrate or protonate at lower pH, which will change the electronic structure as well as its optical property. ,, As a result, the 2-IC absorption at λ max = 288 nm will decrease under acidic conditions, , consequentially inactivating the photochemical activity of 2-IC (Figure S2a). Another study also showed that the hydration carbonyl group on DMB is possible in acidic media; however, this is more pronounced at pH < 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the intensity of the carbonyl group maximum absorption (λ max ) depends not only on the nature of substituent around the aldehyde/ketone group but also on the pH and the type of solvent. Several studies have been done on the pH dependency; in 2-IC for instance, the aldehyde group will hydrate or protonate at lower pH, which will change the electronic structure as well as its optical property. ,, As a result, the 2-IC absorption at λ max = 288 nm will decrease under acidic conditions, , consequentially inactivating the photochemical activity of 2-IC (Figure S2a). Another study also showed that the hydration carbonyl group on DMB is possible in acidic media; however, this is more pronounced at pH < 2 .…”
Section: Resultsmentioning
confidence: 99%
“…53 Third, the acidity of the media may deactivate the photochemical activity of the photosensitizers because it could foster the hydration of the original carbonyl group to a diol, which then is not photoactive anymore in the actinic region of the spectrum. 20,54,55 MVK and MACR are the first generation oxidation products of isoprene. 56−58 In addition, biogenic emissions, biomass burning, secondary formation, diesel, and gasoline vehicle emissions are potential sources of MVK and MACR, although secondary formation is the largest contributor to MACR and MVK in the atmosphere.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, the measured MACs for the GL + AS BrC samples are also qualitatively similar to samples synthesized from methylglyoxal + ammonia/methylamine with MACs of ∼10 2−3 cm 2 /g in the near-UV. 13,16,56 However, using glyoxal as a precursor will generate primarily aldehydes as opposed to ketones when using methylglyoxal as a precursor. Aldehydes undergo more efficient hydration than ketones in aqueous solution resulting in the destruction of the carbonyl chromophore and leading to weaker overall absorption.…”
Section: Uv−vis Absorption Spectra and Decaymentioning
confidence: 99%
“…Moreover, a shoulder around 370 nm was observed for 3,6-dioxa-1,8-octanedithio- bis -carbonylimidazole as a result of the n–π* electron transitions of the imidazole moieties. 51 Meanwhile, as a maximum emission wavelength of 423 nm was detected at λ exc = 340 nm for P2 , 3,6-dioxa-1,8-octanedithio- bis -carbonylimidazole and MC were subjected to analogue analysis; a slightly lower maximum emission wavelength of 351 nm was recorded at λ exc = 340 nm. The intensity of 3,6-dioxa-1,8-octanedithio- bis -carbonylimidazole was slightly higher in comparison with that of MC (185 vs. 140 a.u.…”
mentioning
confidence: 99%